PENGARUH JENIS PENGETAHUAN DAN KECAKAPAN TERHADAP KEMAMPUAN MENULIS BAHASA INGGRIS PADA MAHASISWA TEKNIK MESIN SEKOLAH TINGGI TEKNIK PLN - Redaksi Tim Jurnal (JURNAL POWERPLANT, 2018)
The purpose of this study was to investigate the effects of genre knowledge and sentence structure toward dtudent’s writing skill in recount text in STT PLN Jakarta.In this research, the writer uses survey methodology with approach to correlation.The result of study identivies : 1 ) There is an effect of significant genre knowledge and sentence structure toward student’s writing skill in recaoun text with coefficient correlation multiple Ry 12 = 0.811.Genre knowledge and sentence structure to give 65.8 % toward variation student’s writing skill in recount text via similarity multiple regression Y = 34.466 + 0.793 x 1 + 0.602 x 2 which significant to standard 0.05. In relation to result of the recearch significant exam is able to F account = 35.563 > F table = 3.25. 2) There is an effect which significant genre knowledge toward student’s writing skill in recauntext variable genre knowledge the way of effecttive give 64.3 % toward variation student’s writing skill in recaunt text. The result of the researce significant is able to t account ( 4.836 ) > t table ( 1.69 ) to standart real 5 % . 3 There is an effects significant between sentence structure student’s writing skill in recaount text .Variable sentence structure the of evective give 35.7 % toward variation student’s skill in recount text .The result of significant is able to t account ( 3. 058 ) < t table ( 1.69 ) to standard real 5 %.